Fused arene-functionalized polyhedral oligomeric silsesquioxanes as thermoelectric materials1. Issue 47 (27th May 2015) - Huzyak, Paige; Ferguson, John; Sharpensteen, Jeremiah; Xu, Lan; Ananthakrishnan, Soundaram Jeevarathinam; Rathnayake, Hemali
<x xml:space="preserve">Abstract</x> Two derivatives of fused-arene functionalized polyhedral oligomeric silsesquioxanes (POSS-ANT and POSS-PDI-POSS) were synthesized and their electronic properties were studied for organic-based thermoelectric devices.